Research Literacy Workshop for Indonesian Language Teachers: Designing Scientific Inquiry-Based Explanatory Text Learning from Reliable Sources - Damayanti, Deasy Aditya; Yosep, Yosep Tri Nur; Mariyana, Tina; Medianingsih, Sri Mariyana; Suhartati, Suhartati Mariyana; Marfuah, Siti Mariyana; Nurafni, Sinta; Rahmasya AS, Shela Siti; Fitriani, Sakinah Siti (Fakultas Kewirausahaan Universitas Garut, 2024)
This descriptive study explores the implementation of the